Transforming growth factor beta in normal human lung: preferential location in bronchial epithelial cells. - Magnan, A. (1994)
BACKGROUND--Transforming growth factor beta (TGF-beta) is an immunomodulatory cytokine regulating the proliferation and differentiation of various cell types. It also contributes to the maintenance of tissue architecture by influencing the production of extracellular matrix components. TGF-beta has been detected in bronchoalveolar lavage fluid from normal human lung, but the nature and distribution of cells containing TGF-beta in this organ remain unknown. METHODS--Fourteen normal human lung specimens were studied by immunohistochemistry with a monoclonal antibody recognizing TGF-beta 1, TGF-beta 2 and TGF-beta 3. RESULTS--TGF-beta was detected in all cases. Bronchial epithelial cells contained the largest amounts of TGF-beta. In these cells the staining was brightest at the apical pole. Macrophages and smooth muscle cells also contained TGF-beta, although less than epithelial cells. No TGF-beta was detected in other cell populations, including endothelial cells, fibroblasts, and pneumocytes. CONCLUSIONS--The bronchial epithelial compartment appears to be the main location of TGF-beta in the normal human lung, suggesting that this cytokine has a pivotal role in the immunological properties of the bronchial mucosa.